Social Theory : A Reader (Edinburgh University Press, 2005)
Covering a wide area of political sociology and social and political theory, this Reader offers a selection of extracts incorporating both primary and secondary readings. As well as a general introduction to the concept of social theory, each section is prefaced by an introduction to the relevant theorist(s) and each reading is accompanied by a short explanatory introduction.Including a broad range of texts, the book offers a general introduction to the main writings of political sociology and social theory. While other texts tend to focus either on either traditional or contemporary figures, this Reader is unique in tracing a connecting strand from the work of Marx, Weber and Durkheim to more contemporary social theorists. And by focusing on the theories of social conflict, cohesion and consent it also acts as a guide to issues in sociological, political and cultural analysis.Includes sections on:* Marx and Engels* Gramsci* Durkheim and Parsons* Weber* The Frankfurt School (Adorno and Horkheimer